P-034 Brief Behavioral Intervention for Sleep Disturbance for Adolescents and Young Adults with Crohn's Disease: Open Trial Study. (March 2016) - Szigethy, Eva; Hashash, Jana; Vachon, Ashley; Mcauliff, Katheryn; Strassburger, Meredith; Rode, Noelle; Keljo, David; Fabio, Anthony; Regueiro, Miguel; Binion, David; Lotrich, Francis; Germain, Anne
Abstract : Background: Sleep disturbance is common in patients with Crohn's disease (CD) and has been associated with fatigue and increased disease activity. Behavioral interventions for insomnia have improved sleep and associated fatigue in other populations but have not been tested in young adults with IBD. This study presents results of an open trial over 3 months of Brief Behavioral Therapy for Sleep in IBD (BBTS-I) in adolescents and young adults with CD to evaluate feasibility and effects on insomnia and fatigue. Methods: Over 18 months, we screened all CD subjects ages 15 to 30 using the Pittsburgh Sleep Quality Index (PSQI) and Multidimensional Fatigue Inventory (MFI) at pediatric or adult GI clinic appointments. Participants scoring ≥7 on PSQI and ≥45 on MFI completed a further assessment which included further probes of sleep using subjective (questionnaires) and objective (actigraphy) measures, a structured psychiatric interview for DSM-IV (SCID). The BBTS-I consisted of 2 to 4 sessions consisting of sleep hygiene, behavioral strategies, and hypnosis delivered in either face-to-face or phone sessions. Primary outcomes were PSQI and MFI; secondary outcomes were anxiety and depression severity (Hamilton Rating Scale; HRSA and HRSD), CD activity (Harvey Bradshaw [HB]), and quality of life (Short Inflammatory Bowel Disease Questionnaire; SIBDQ. Paired t -test was used to evaluate pre-post differences in outcomes. The relationship between change in sleep, fatigue, and CD activity over time was also explored. Results: Over 18 months, 224 CD subjects were approached, 193 screened; 93 screened positive and 51 completed a more comprehensive assessment; and 48 participated in the BBTS-I intervention. Subjects receiving the intervention were predominantly Caucasian, 63% female, with mean age of 23.5 and mild mean CD activity. Baseline mean PSQI was 10.8 (SD 3.2) and MFI was 64.6 (SD 11.2). Anxiety disorders and depression was common and mean HRSA of 13.1 (SD 7.2); mean HRSD of 13.1 (SD 4.8), and mean SIBDQ of 45.7 (SD 9.4) at baseline. 72% of the sample participated in the intervention. After BBTS-I, there was a significant reduction in PSQI (mean change, 4.036; P < 0.001; η 2 = 0.57) and MFI (mean change, 11.97; P < 0.001; η 2 = 0.53) over time. There were also significant pre-post increase in SIBDQ ( P < 0.001; η 2 = 0.61) and reduction of HRSD ( P = 0.001; η 2 = 0.42), HB ( P = 0.001; η 2 = 0.34), and HRSA ( P = 0.04; η 2 = 0.25). Improvement of PSQI over time was not significantly correlated with changes in MFI, HB, HRSA, or HRSD. Improvement in MFI over time was significantly correlated with improvements in HRSA (r = 0.75; P < 0.001) and HRSD (r = 0.47; P = 0.007) but not improved PSQI or HB over time. Conclusions: Using a brief behavioral intervention for sleep disturbance in young adults with CD is feasible and has promising effects in improving sleep, fatigue, quality of life, anxiety, depression and CD activity. Improvement in sleep over time after the intervention does not appear related to changes in disease activity or mood symptoms while improvement in fatigue is related to improvements in anxiety and depression. Randomized trials with larger samples will be needed to show that behavioral intervention for sleep is efficacious in patients with IBD.